2020
DOI: 10.1186/s12879-020-04958-z
|View full text |Cite
|
Sign up to set email alerts
|

Anemia risk factors among people living with HIV across the United States in the current treatment era: a clinical cohort study

Abstract: Background: Anemia is common among people living with HIV infection (PLWH) and is associated with adverse health outcomes. Information on risk factors for anemia incidence in the current antiretroviral therapy (ART) era is lacking. Methods: Within a prospective clinical cohort of adult PLWH receiving care at eight sites across the United States between 1/2010-3/2018, Cox proportional hazards regression analyses were conducted among a) PLWH free of anemia at baseline and b) PLWH free of severe anemia at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 36 publications
7
46
3
1
Order By: Relevance
“…A retrospective cohort study showed that a lower CD4 + T lymphocyte count was associated with anemia and severe anemia and that women with a CD4 + T lymphocyte count of <100 cells/μL were at an increased risk of developing anemia. 12 Also, blood hemoglobin levels, mean corpuscular volume and mean corpuscular hemoglobin were shown to be lower in PLWHA with a CD4 + T lymphocyte count of <200 cells/μL than in PLWHA with asymptomatic HIV infection. 4 …”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…A retrospective cohort study showed that a lower CD4 + T lymphocyte count was associated with anemia and severe anemia and that women with a CD4 + T lymphocyte count of <100 cells/μL were at an increased risk of developing anemia. 12 Also, blood hemoglobin levels, mean corpuscular volume and mean corpuscular hemoglobin were shown to be lower in PLWHA with a CD4 + T lymphocyte count of <200 cells/μL than in PLWHA with asymptomatic HIV infection. 4 …”
Section: Resultsmentioning
confidence: 87%
“…In a recent cohort study of PLWHA receiving care at eight sites across the USA, 7.2% of individuals developed anemia after 6 y of follow-up, indicating an incidence of anemia of 1.95/100 person-years. 12 In Denmark, a longitudinal study detected the prevalence of 6.9% of anemia; however, PLWHA evaluated had an undetectable viral load, which may have contributed to the low rate of anemia observed. 15 …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations